Regional developments [In 2017 Global Food Policy Report] - Makombe, Tsitsi; Collins, Julia; Badiane, Ousmane; Breisinger, Clemens; Abdelaziz, Fatma; Khouri, Nadim; Akramov, Kamiljon T.; Park, Allen; Ilyasov, Jarilkasin; Kumar, Anjani; Ahmed, Akhter; Davies, Stephen; et al. (International Food Policy Research Institute, 2017)
2016 saw important developments with potentially wide repercussions for food security and nutrition in individual countries and regions. This section offers perspectives on food policy developments across the major regions: Africa, the Middle East and North Africa, Central Asia, South Asia, East Asia, and Latin America and the Caribbean. Urbanization trends and related impacts on food security and nutrition are presented for each region. The individual regional sections cover many other critical topics: Acceleration of cooperation and investment in Africa to improve food security in the face of climate challenges and low commodity prices; Continuing conflict in the Middle East and North Africa, while some countries begin to face policy reform needs and realities of low oil prices; Central Asia’s promotion of agricultural diversification and regional integration to increase economic resilience; South Asia’s rapid growth and new investments and policies in the agriculture sector; Urbanization, changing diets, and regional growth in East Asia Recession in major economies of Latin America and the Caribbean along with El Niño’s effects on regional prospects.